Kompetensi guru perspektif Imam Bukhari dalam Kitaabul Ilmi Shahih Bukhari - Abdurrohman, Muhammad Cholid; Lisnawati, Santi; Indra, Hasbi (Tawazun: Jurnal Pendidikan Islam, 2022)
Teachers in education are figures who have an important role. He is an agent of change responsible for transferring knowledge and internalizing values to students. Therefore, competencies are needed to support their duties properly so that educational goals can be achieved optimally. This paper aims to examine the competence of teachers from the perspective of Imam Bukhari in Kitaabul Ilmi Sahih Bukhari, considering that the book is an important reference book in Islamic studies. This research was conducted with a qualitative method with library research. The primary data source in this study was Kitaabul Ilmi Sahih Bukhari. Based on research data, teachers must possess spiritual, pedagogic, professional, personality, and social competencies. Of the five competencies, spiritual competence is the most important. It is the basis for other competencies because Islamic education is an interaction between educators and students and is also influenced by divine values because the main educator in Islamic education is essentially Allah The Almighty. Abstrak Guru dalam pendidikan adalah tokoh yang memiliki peran penting. Ia adalah seorang agen perubahan yang bertanggung jawab dalam transfer ilmu pengetahuan dan internalisasi nilai pada peserta didik. Oleh karena itu dibutuhkan kompetensi yang dapat menunjang tugasnya dengan baik agar tujuan pendidikan dapat dicapai dengan maksimal. Tulisan ini bertujuan untuk mengupas kompetensi guru dalam perspektif Imam Bukhari dalam Kitaabul Ilmi Shahih Bukhari mengingat kitab tersebut adalah kitab rujukan penting dalam studi Islam. Penelitian ini dilakukan dengan metode kualitatif dengan jenis library research. Sumber data primer pada penelitian ini adalah Kitaabul Ilmi Shahih Bukhari. Berdasarkan data penelitian maka kompetensi yang harus dimiliki guru adalah kompetensi spiritual, pedagogi, profesional, kepribadian dan sosial. Dari lima kompetensi tersebut kompetensi spiritual adalah yang paling penting dan merupakan dasar bagi kompetensi lainnya, karena pendidikan Islam bukan hanya interaksi antara pendidik dan peserta didik saja akan tetapi dipengaruhi juga oleh nilai ketuhanan karena pada pendidik utama dalam pendidikan Islam pada hakikatnya adalah Allah azza wa jalla.